An Interactive Multimedia Approach to Bilingual Worksheets for Optimizing Language Learning in Young Children - Intan Maulida Qorry’ Aina (Journal of Early Childhood Education Studies, 2025)
This study examines the efficacy of an interactive multimedia method utilized in bilingual worksheets to enhance language acquisition in young children. This strategy incorporates auditory, visual, and kinesthetic elements, accommodating various learning styles and improving cognitive engagement. The research methodology entails an exhaustive evaluation of material, including existing studies, educational papers, and multimedia resources pertinent to bilingual language acquisition and interactive learning instruments. Research demonstrates that multimedia bilingual worksheets enhance vocabulary retention, pronunciation precision, and student motivation in contrast to conventional static worksheets. Challenges including technological accessibility and educator readiness are examined, along with practical ramifications for curriculum writers and instructors. This study offers significant insights into the transformative potential of interactive multimedia in early childhood bilingual education, enhancing inclusivity and efficacy in language acquisition.